Enhancing Students’ Mathematical Communication Skills through Reciprocal Teaching - Jeprizal Jeprizal; Zulfah Zulfah; Astuti Astuti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical communication is a key competence in mathematics learning because it enables students to express ideas, justify reasoning, and represent mathematical thinking clearly. This study examined the effect of Reciprocal Teaching on eighth-grade students’ mathematical communication skills at SMP Negeri 1 Bangkinang. A quasi-experimental design with a nonequivalent control group was employed. The participants were divided into an experimental group taught through Reciprocal Teaching and a control group taught through conventional instruction. Data were collected using pretest and posttest measures of mathematical communication skills. The results showed that the experimental group obtained a higher posttest mean score (83.65) than the control group (72.67). The independent samples t-test indicated a significant difference between the two groups, p < .001. The N-gain score of the experimental group was high (0.73), whereas that of the control group was moderate (0.54). The effect size was also large (Cohen’s d = 1.528), indicating that Reciprocal Teaching had a substantial effect on students’ mathematical communication skills. These findings suggest that Reciprocal Teaching can be used as an instructional approach to support mathematical communication in junior secondary mathematics classrooms.